RISK MANAGEMENT IN ROAD DEVELOPMENT PROJECTS REGENCY. KUTAI TIMUR, EAST KALIMATAN PROVINCE - Rizki Ayu Saraswati (Magister Teknik Sipil Pps Universitas Muslim Indonesia, 2021)
risk management from the start of a project to its completion, starting from actively identifying risks, then assessing the levels of these risks so that management priorities are obtained, and determining the handling steps so that risks can be minimized as much as possible. This study aims to (1) identify risks during the construction of the Sp.Perdau – Plb Road Reconstruction project. Ronggang (Sangkulirang), (2) Analyzing the most dominant risks that occur in the Sp. Road Reconstruction project. Perdau – Plb. Ronggang (Sangkulirang) in order to improve project quality performance and (3) Knowing the risk response of the most dominant risks that occur in the Sp. Road Reconstruction project. Perdau – Plb. Ronggang (Sangkulirang). The results showed that (1) 53 out of 95 risk variables occurred in the construction of the sp. reconstruction Preservation project. Perdau-ma. Lembak-port of carang (sangkulirang), (2) the dominant risk in this project is to use the Probablity x Impact table on both cost and time. From this analysis, it was found that 9 risk variables occurred and had a significant impact on costs